Formulation and Evaluation of Topical Gel of Ketoprofen Using Different Polymers - Ramchandani, U (International Journal of Pharmaceutical & Biological Archive, 2013)
Formulation and Evaluation of Topical Gel of Ketoprofen Using Different Polymers